Affective dimensions of pandemic life: The mediatised cultivation of outrage. (8th December 2021) - Conradson, David
Abstract: The mediatised circulation of narratives that invite or induce strong emotional responses has been a key dimension of the COVID‐19 pandemic. These circulations have shaped the affective dimensions of pandemic life—including collective feelings of fear, anger, relief and happiness—while also contributing to polarised debates regarding lockdowns and vaccinations. In this context, this commentary examines the emergence of public outrage in Aotearoa New Zealand over two women alleged to have broken a lockdown travel restriction. It describes an escalation of judgement and anger, and considers whether the mediatised cultivation of such feelings might displace or undermine empathy and civility.